Rescue technique for trapped bone needle in cement cast. (19th January 2022) - Dimancea, Alexandru; Premat, Kevin; Shotar, Eimad; Cormier, Evelyne; Chiaroni, Pierre-Marie; Mahtout, Jugurtha; Clarençon, Frédéric
Abstract : Avascular necrosis, or Kummel disease, is a potential complication of vertebral compression fractures. It is believed to arise as a result of a failed fracture healing process, 1 2 leading to the formation of an air or fluid filled cavity within the vertebral body. 3 Percutaneous vertebroplasty seems to provide both pain relief and increased spinal stability in avascular necrosis. 4 In this technical video, we present the case of an osteoporotic patient with a complicated vertebroplasty, caused by trapping of the bone needle inside the intravertebral cement cast. Two methods were used sequentially, leading to retrieval of the bone needle. We identified several technical aspects, such as injection speed, quasi-filling of the vertebral cavity, and frequent rotation of the bone needle as essential for the success of the procedural. We suggest that improving these parameters may prevent intravertebral bone needle trapping in patients with avascular necrosis.